(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The genetic diversity among a group of 20 sorghum accessionsfrom Sudan were assessed with RAPD molecular marker. Out of 572amplified PCR bands scored, 61.1% were polymorphic. Estimates of thegenetic similarity among the accessions ranged from 60% to 93%. Adendrogram, constructed on the basis of similarly matrix data, categorizedthe accessions into two main groups: a major one comprising nine groupsinvolving 14 accessions and a smaller one consisting of two groupsinvolving four accessions. The race Caudatum and its hybrids and theDurra race and its hybrids were detected in 18 and 16 of the accessionstested, respectively, whereas the races Bicolor and Guinea wererepresented each by only one accession and Kafir by two accessions.There was agreement between the relationships revealed by molecularcharacterization and those reflected by racial classification in some casesbut not in others. Thus, in future, to ensure a more complete andinformative characterization of the germplasm., both molecular andmorphological methods should be used.